2008
DOI: 10.1371/journal.pntd.0000233
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Genetic Variation of Triatoma dimidiata, the Main Chagas Disease Vector in Central America, and Its Position within the Genus Triatoma

Abstract: BackgroundAmong Chagas disease triatomine vectors, the largest genus, Triatoma, includes species of high public health interest. Triatoma dimidiata, the main vector throughout Central America and up to Ecuador, presents extensive phenotypic, genotypic, and behavioral diversity in sylvatic, peridomestic and domestic habitats, and non-domiciliated populations acting as reinfestation sources. DNA sequence analyses, phylogenetic reconstruction methods, and genetic variation approaches are combined to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
220
3
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(254 citation statements)
references
References 71 publications
(111 reference statements)
23
220
3
8
Order By: Relevance
“…However, "subspecies are local populations that are recognisably different from each other but they are nevertheless considered to belong to the same species, because they are observed to interbreed in nature or because it is inferred that they are likely to interbreed" (Mayr & Diamond 2001). In accordance with these species and subspecies concepts and in light of some previously published reports (Flores et al 2001, Martínez et al 2005, Takashi-Obara et al 2007, Bargues et al 2008, the biological evidence reported here supports the proposition that it is more appropriate to attribute a subspecies level to M. bassolsae, as has been proposed for M. pallidipen nis, M. longipennis and M. picturatus (Martínez-Ibarra et al 2008b). However, the same biological evidence supports the proposal that M. phyllosomus is a full spe cies, as some recent molecular studies have proposed (Sainz et al 2004, Pfeiler et al 2006.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, "subspecies are local populations that are recognisably different from each other but they are nevertheless considered to belong to the same species, because they are observed to interbreed in nature or because it is inferred that they are likely to interbreed" (Mayr & Diamond 2001). In accordance with these species and subspecies concepts and in light of some previously published reports (Flores et al 2001, Martínez et al 2005, Takashi-Obara et al 2007, Bargues et al 2008, the biological evidence reported here supports the proposition that it is more appropriate to attribute a subspecies level to M. bassolsae, as has been proposed for M. pallidipen nis, M. longipennis and M. picturatus (Martínez-Ibarra et al 2008b). However, the same biological evidence supports the proposal that M. phyllosomus is a full spe cies, as some recent molecular studies have proposed (Sainz et al 2004, Pfeiler et al 2006.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with a previous study (Martínez-Ibarra et al 2008b), where M. mazzottii was reproductively isolated from the four species of Meccus examined (M. phyllosomus was not included in that study). Our results, in combination with results showing little or no genetic differences between these species (Bargues et al 2008) indicate that these species are closely related and have diverged very recently.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Las diferencias observadas en los rangos y en el tiempo medio de duración del ciclo de vida de la cepa colombiana utilizada en este estudio con respecto otras cepas de Centroamérica y Colombia, pueden deberse a las condiciones previas al ensayo, como el tiempo de colonización en el laboratorio; a variaciones de las condiciones del laboratorio en el ensayo, o a diferencias de taxonomía numérica (phenetics) y genéticas de la población ya demostradas para esta especie (32)(33)(34).…”
Section: Hipótesis De Variaciones Entre Ciclos De T Dimidiataunclassified